The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00216-008-2324-1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of microheterogeneity in solid samples using µXRF

Abstract: Micro X-ray fluorescence (microXRF) has been used nondestructively to investigate elemental heterogeneity by constructing two-dimensional maps of elemental concentrations in reference materials. microXRF probes sample sizes well below the 100 mg mass usually recommended for reference materials by NIST. Multivariate methods of analysis, such as principal-component analysis (PCA), show promise in identifying whether "nugget" effects exist within a material, where an element is enriched in small, isolated areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…bottles, ingots, or vials) as well as within units. For evaluations of single samples, a method using PCA has already been demonstrated that compares the behaviors of constituent elements and enables the analyst to calculate the estimated minimum mass for each element 6. This approach for estimating heterogeneity within a sample can be extended to cover a set of samples plotting all samples together in principal component space as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…bottles, ingots, or vials) as well as within units. For evaluations of single samples, a method using PCA has already been demonstrated that compares the behaviors of constituent elements and enables the analyst to calculate the estimated minimum mass for each element 6. This approach for estimating heterogeneity within a sample can be extended to cover a set of samples plotting all samples together in principal component space as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown principal component analysis (PCA) to be a useful tool for processing the large amount of data arising from analyses by µXRF 5. Using descriptive statistics of µXRF data instead of the raw data in combination with PCA has yielded a method6 which can predict the minimum amount of sample that can be used with confidence that nugget effects are not contributing significantly to the overall uncertainty. This method was demonstrated for several reference materials, and a minimum recommended sample mass was calculated for Standard Reference Material (SRM) 1577c (Bovine Liver) and compared to another study3 which used Monte Carlo techniques to predict minimum sample size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ). There have been a few studies on RM mapping (Eggins and Shelley , Molloy and Sieber ). One interesting contribution was provided by Molloy and Sieber (), who mapped RMs and fed their results into principal component analysis to determine the presence of nuggets.…”
mentioning
confidence: 99%
“…More recently, beam diameters have been varied with position relative to the sample recorded (at the centre versus the border of the RM sample) before computing the average and standard deviation (Wilson et al 2002, Jochum et al 2005, 2011. There have been a few studies on RM mapping (Eggins andShelley 2002, Molloy andSieber 2008). One interesting contribution was provided by Molloy and Sieber (2008), who mapped RMs and fed their results into principal component analysis to determine the presence of nuggets.…”
mentioning
confidence: 99%